Preliminary Impact of an Adapted Emotion Regulation Intervention for Adolescents with Overweight and Obesity Attempting to Lose Weight. Issue 9 (December 2020) - Hadley, Wendy; Houck, Christopher; Barker, David; Wickham, Brittany; Bogner, Jaclyn; Jelalian, Elissa
ABSTRACT: Objective: This study examines the acceptability, feasibility, and preliminary impact of a program (HealthTRAC) combining 2 efficacious interventions (one targeting emotion regulation [TRAC] and the other a standardized behavioral weight management intervention [SBWC]) to improve weight management outcomes among a sample of adolescents with overweight and obesity. Method: Adolescents with overweight or obesity (N = 38), ages 13 to 17 years, were enrolled and randomized into either the SBWC or HealthTRAC. Data were collected at baseline (before intervention), at the end of the 16-week intervention (postintervention), and 4 months after completing the intervention (4 months). Assessments included adolescent self-reports of intervention acceptability and reported emotion regulation (ER) abilities and caregiver report of adolescent ER skills. Body mass index (BMI) was used to examine the impact on adolescent weight outcomes. Analyses of covariance controlling for baseline values were used to evaluate study outcomes. Results: Eighty-four percent (n = 32) of participants completed the immediate postintervention and 4-month follow-up assessments. Adolescents in both conditions reported high treatment satisfaction. Adolescents randomized to HealthTRAC demonstrated greater reductions in BMI relative to SBWC and reported greater use of emotion regulation skills. Finally, caregivers of adolescents randomized to HealthTRAC also reported greater improvements in emotion regulation abilities among their adolescents at the 4-month follow-up. Conclusion: Findings suggest that the HealthTRAC intervention was acceptable, feasible to deliver, and demonstrated a positive impact on BMI and emotion regulation abilities. These data suggest that ER is related to health decision-making and is relevant to most overweight/obese adolescents seeking to lose weight.